2017 Jakarta Election – Alternative View: Beyond Religion - Chaula Rininta Anindya (2017)
While religion was a major factor in the recent Jakarta election for governor, fear of oppression and social welfare were significant issues framed by Anies-Sandi and successfully used to mobilise voters. Strategic issue-framing could be replicated in the 2019 presidential election to shape political contestation.